2020
DOI: 10.3389/fpsyg.2020.02090
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Students’ Understanding of and Visual Attention on Digitally Represented Graphs Across Two Domains in Higher Education: A Postreplication Study

Abstract: Domain-specific understanding of digitally represented graphs is necessary for successful learning within and across domains in higher education. Two recent studies conducted a cross-sectional analysis of graph understanding in different contexts (physics and finance), task concepts, and question types among students of physics, psychology, and economics. However, neither changes in graph processing nor changes in test scores over the course of one semester have been sufficiently researched so far. This eye-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 75 publications
(215 reference statements)
0
9
0
Order By: Relevance
“…In recent studies, eye-tracking was used to get a closer look at students' response processes [1,3,20] to get an indication of the difficulties of graph understanding. This method enables the analysis of not only the test scores but allows researchers to determine with which frequency and sequence a learner looks at individual parts of a line graph-so-termed Areas of Interest (AOIs)-during the process of task solving (e.g., axis labels, axis tick labels, response options like the attractor or distractor, the curve).…”
Section: Eye-tracking Research On Students' Difficulties In Graph Understandingmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent studies, eye-tracking was used to get a closer look at students' response processes [1,3,20] to get an indication of the difficulties of graph understanding. This method enables the analysis of not only the test scores but allows researchers to determine with which frequency and sequence a learner looks at individual parts of a line graph-so-termed Areas of Interest (AOIs)-during the process of task solving (e.g., axis labels, axis tick labels, response options like the attractor or distractor, the curve).…”
Section: Eye-tracking Research On Students' Difficulties In Graph Understandingmentioning
confidence: 99%
“…Studies that examined the understanding of line graphs in physics and economics contexts considered the dwell times and fixation times on AOIs of a graph and suggested that certain eye-tracking metrics provide initial indications of students' learning difficulties [1,20]. Relevant AOIs (i.e., areas containing critical information, e.g., axes) were viewed longer and with higher frequency by physics students who show a higher understanding of graphs [1,3].…”
Section: Eye-tracking Research On Students' Difficulties In Graph Understandingmentioning
confidence: 99%
See 3 more Smart Citations